Unlocking the Power of Technology: Navigating the Benefits of Integrating ICT in Differentiated Instruction - Auly, Aisyah Noor; Putro, Nur Hidayanto Pancoro Setyo (Formosa Journal of Sustainable Research, 2024)
ICT integration in English as a foreign language (EFL) teaching enhances knowledge acquisition and optimizes learning processes. It facilitates differentiated instruction, addressing diverse student needs and achieving targeted outcomes. This proactive approach adapts content, processes, products, and learning environments to accommodate students’ readiness, interests, and backgrounds, promoting engagement and improved academic outcomes. This study aims to explore the benefits of integrating ICT in differentiated instruction practices in English classrooms. This study uses a qualitative approach with a phenomenological design. Combining interviews with English teachers, classroom observations, and analysis of supporting documents to comprehensively understand the phenomenon. This study was conducted in three vocational high schools in Yogyakarta. The results showed that the benefits of ICT integration in differentiated instruction include improved student conceptual understanding, as evidenced by students’ ability to grasp the material and express their ideas through classroom activities. Additionally, ICT increases student engagement, with students showing motivation, interest, active participation, and improved collaboration in the classroom. Another key benefit is student self-development, fostering creativity, confidence, discipline, and responsibility